Determinants of Stock Prices in the Indonesian Stock Exchange - Tannar, Oryza (Jurnal Mebis, 2025)
The main objective of financial reports is to provide useful accounting information for making economic decisions. Users of financial reports will use them to predict, compare and assess the financial information impacts arising from the economic decisions they make. This study aims to determine the effect of return on assets, return on equity, and net profit margin. The type of research conducted in this study is research using quantitative techniques in multiple regression analysis. The results of this study show that return on assets has a significant effect on stock prices, while return on equity and net profit margin do not have a significant effect on stock prices. Then, Return on Assets received by the company is more dominant in influencing Stock Price. In general, the higher the ROA, the greater the Stock Price, because investors tend to dare or like healthy companies or can provide high profits